Impact of different tissue dissociation protocols on endothelial cell recovery from developing mouse lungs - Palumbo, Francesco; Gunjak, Mis̆a; Lee, Patty J.; Günther, Stefan; Hilgendorff, Anne; Vadász, István; Herold, Susanne; Seeger, Werner; Mühlfeld, Christian Axel; Morty, Rory E. (Cytometry, 2024)
Flow cytometry and fluorescence-activated cell sorting are widely used to study endothelial cells, for which the generation of viable single-cell suspensions is an essential first step. Two enzymatic approaches, collagenase A and dispase, are widely employed for endothelial cell isolation. In this study, the utility of both enzymatic approaches, alone and in combination, for endothelial cell isolation from juvenile and adult mouse lungs was assessed, considering the number, viability, and subtype composition of recovered endothelial cell pools. Collagenase A yielded an 8-12-fold superior recovery of viable endothelial cells from lung tissue from developing mouse pups, compared to dispase, although dispase proved superior in efficiency for epithelial cell recovery. Single-cell RNA-Seq revealed that the collagenase A approach yielded a diverse endothelial cell subtype composition of recovered endothelial cell pools, with broad representation of arterial, capillary, venous, and lymphatic lung endothelial cells; while the dispase approach yielded a recovered endothelial cell pool highly enriched for one subset of general capillary endothelial cells, but poor representation of other endothelial cells subtypes. These data indicate that tissue dissociation markedly influences the recovery of endothelial cells, and the endothelial subtype composition of recovered endothelial cell pools, as assessed by single-cell RNA-Seq.